Negosiasi, Mediasi Hingga Perlindungan Pengabaian Hak Asuh Anak Akibat Perceraian Dan Penyelesaian Sengketa Pemeliharaan Anak - Riana Hasyim; Mutia CH. Thalib; Sri Nanang M.Kamba (Universitas Sains dan Teknologi Komputer, 2024)
Child maintenance is an important aspect that needs to be considered in the divorce process. The aim of this writing is to find out the Settlement of Child Maintenance Disputes (Alimentation for Post-Divorce Consequences). The research method used is normative legal research (normative law research) using normative case studies, namely in the form of legal behavioral products, which are based on legal norms or legal rules that apply in Indonesian society. The main aim of resolving child maintenance disputes is to ensure the welfare and best interests of the child. This involves ensuring the child receives adequate financial support from the parent who does not live with them. In some cases, resolving child maintenance disputes involves legal proceedings involving family courts. This process involves the filing of documents, a hearing, and a court decision that will determine the amount and method of child support payments.